In vitro and in vivo antifungal activity of Allium hirtifolium and Allium sativum - Alireza Diba; Fahimeh Alizadeh (Mashhad University of Medical Sciences, 2018)
Objective: One of the major clinical problems is the resistance of Candida speciestowards most of antifungals. The search for new antifungal drug from plants have helped to overcome this problem. This study evaluated the effects of Allium hirtifolium and Allium sativumextracts on Candida tropicalis both in vitro and in a mouse model of systemic candidiasis. Materials and Methods: In this study, clinical isolates of C. tropicalis were isolated and identified from immunocompromised patients with recurrent candidiasis. Antifungal susceptibilities assessment and time kill study of aqueous and ethanolic extracts of A. hirtifolium and A. sativumextracts were done against C. tropicalis. The in vivo activity of aqueous extracts of A. hirtifolium and A. sativumwere evaluated in a mouse model of systemiccandidiasis caused by C. tropicalis through estimating the host survival time, fungal burden and histopathologic analyses. Results: The aqueous and ethanolic extracts of A. hirtifolium and A. sativum exhibited significant antifungal activity against C. tropicalis. In time kill study, A. hirtifolium and A. sativum extracts exhibited significant effects against C. tropicalis (p